2014
DOI: 10.1038/tp.2013.117
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of schizophrenia-related genes and electrophysiological measures reveals ZNF804A association with amplitude of P300b elicited by novel sounds

Abstract: Several genes have recently been identified as risk factors for schizophrenia (SZ) by genome-wide association studies (GWAS), including ZNF804A which is thought to function in transcriptional regulation. However, the downstream pathophysiological changes that these genes confer remain to be elucidated. In 143 subjects (68 clinical high risk, first episode or chronic cases; 75 controls), we examined the association between 21 genetic markers previously identified by SZ GWAS or associated with putative intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 99 publications
0
26
1
Order By: Relevance
“…Firstly there are no significant differences between groups in median amplitude (c.f. O'Donoghue et al, 2014;Del Re et al, 2014). Secondly even when controlling for non-significant differences, our effects hold.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Firstly there are no significant differences between groups in median amplitude (c.f. O'Donoghue et al, 2014;Del Re et al, 2014). Secondly even when controlling for non-significant differences, our effects hold.…”
Section: Discussioncontrasting
confidence: 42%
“…Evidence is mixed on its structural correlates -some studies find no association of rs1344706 and volumetric measures (Cousijn et al, 2014;Sprooten et al, 2012) or white matter integrity (Kuswanto et al, 2012;Wei et al, 2013), while others find associations with white matter volume (Wassink and Epping, 2012), white matter integrity (Ikuta et al, 2014), or grey matter volume . ERP studies have also identified elevated auditory P300 amplitude in risk allele carriers (O'Donoghue et al, 2014;Del Re et al, 2014).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 94%
See 1 more Smart Citation
“…Walters et al also found that schizophrenia patients who carried the rs1344706 risk allele performed better on working memory and episodic memory tasks. Recent studies showed that the rs1344706 T-allele was related to an increase in novel P300b amplitude, which is lower in patients than in controls (Del Re et al, 2014;O'Donoghue et al, 2014). This positive dose effect of the T-allele was also found with regard to attention, memory, language-relevant processes, and processing speed (Balog et al, 2011;Becker et al, 2012;Cummings et al, 2010;Walters et al, 2010), indicating that this risk allele may exert a protective effect on cognitive performance in schizophrenia.…”
Section: Genetic Associationmentioning
confidence: 89%
“…COMT has been associated with amplitude (Gallinat et al 2003;Golimbet et al 2006) and NRG1 with latency (Kang et al 2012) and a significant association was reported between the P300 amplitude elicited by novel sounds (P3b component) and ZNF804A (Del Re et al 2014). …”
Section: Associations Between Endophenotypes and Susceptibility Genesmentioning
confidence: 95%